Comparison of the bacterial communities in home-made Nanfeng yancai with and without salt. (November 2019) - Liu, Zhanggen; Li, Junyi; Huang, Tao; Xiao, Yangsheng; Peng, Zhen; Xie, Mingyong; Xiong, Tao
Abstract: The differences in bacterial communities and physicochemical characteristics between salted and salt-free yancai samples from Nanfeng County were compared in this study. Total acid, salinity and lactic acid content in salted group were significantly higher than those in salt-free group, whereas pH value as well as the contents of acetic acid, sucrose, glucose and fructose showed no significant difference between the two groups. 20 phyla, 339 genera and 203 species were observed in all yancai samples. Firmicutes and Proteobacteria were the major phyla. Lactobacillus was the predominant genus in both the salted and the salt-free samples, whereas Pediococcus, as the second most abundant genus in the salted samples, was in fairly low abundance in the salt-free samples. Culture-dependent and -independent methods showed that the major lactic acid bacteria in the salted samples were Lactobacillus plantarum, L. pentosus, Pediococcus pentosus and L. brevis, while the salt-free samples were predominated by L. fermentum, L. coryniformis and L. sp. The result indicated that salinity had a significant effect on the bacterial communities in Nanfeng yancai, which will improve our understanding of the bacterial ecology of yancai, as well as the relationships between physicochemical characteristics and the microbiota of yancai. Graphical abstract: Unlabelled Image Highlights: Bacterial communities and physicochemical properties in yancai were investigated. The most abundant genus was Lactobacillus in yancai. Pediococcus was more abundant in the salted yancai than that in salt-free yancai. Salted yancai was dominated by Lactobacillus plantarum, L. pentosus and Pediococcus Pentosaceus . Lactobacillus fermentum, L. coryniformis and L. sp. were the major species in salt-free yancai.